1998
DOI: 10.1089/lap.1998.8.167
|View full text |Cite
|
Sign up to set email alerts
|

Obstructing Internal Hernia Complicating Totally Extraperitoneal Inguinal Hernia Repair

Abstract: A case is presented of a totally extraperitoneal laparoscopic hernia repair complicated by internal herniation of small bowel through an inadvertent peritoneal defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This case has been compared with the previously reported similar cases, it has been noted the bowel strangulation happened at sixth day while in the case reported by Azurin et al ,2 the bowel was strangulated for 48 hours postoperatively. The other cases reported by Rink et al 6 and Lodha et al 7 showed small bowel obstruction with no strangulation. Delayed presentation with strangulation suggesting that the bowel had been herniating slowly through the peritoneal defect into the preperitoneal space over the first few subsequent days, probable big preperitoneal space was accommodating the bowels efficiently until a reasonably long segment of the bowel had herniated and incarcerated and eventually strangulated due to narrow peritoneal defect.…”
Section: Discussionmentioning
confidence: 75%
“…This case has been compared with the previously reported similar cases, it has been noted the bowel strangulation happened at sixth day while in the case reported by Azurin et al ,2 the bowel was strangulated for 48 hours postoperatively. The other cases reported by Rink et al 6 and Lodha et al 7 showed small bowel obstruction with no strangulation. Delayed presentation with strangulation suggesting that the bowel had been herniating slowly through the peritoneal defect into the preperitoneal space over the first few subsequent days, probable big preperitoneal space was accommodating the bowels efficiently until a reasonably long segment of the bowel had herniated and incarcerated and eventually strangulated due to narrow peritoneal defect.…”
Section: Discussionmentioning
confidence: 75%
“…The likely cause is either an unrecognized or unrepaired peritoneal defect during dissection. Although there are several case studies reported in the literature, the incidence of bowel obstruction post laparoscopic hernia repair is infrequent. This is reported to be 0.28%, with transabdominal pre‐peritoneal hernia repairs having a higher occurrence of bowel obstruction (0.5%) in comparison to TEP repairs (0.07%) .…”
mentioning
confidence: 99%